La Constitution canadienne et la réglementation des relations économiques internationales au sortir du « Tokyo Round » - Bernier, Ivan (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1979)
Following the conclusion of the recent multilateral trade negotiations under the auspices of G.A.T.T. (Tokyo Round), a number of agreements have been concluded in the field of non-tariff measures that may well give, in the future, a new impetus to the exercise of the federal power over "trade and commerce". Indeed, there appears to be a growing tendency, both at the international level and in our constitutional law, to recognize that international economic relations start and end with internal economic considerations. The importance of this development has not escaped the attention of the provinces which, in recent years, have attempted in various ways to promote their interest at the international level, while claiming, at the same time, a greater input in the formulation of the national economic policy. The object of this paper is to take a global look at this development. In conclusion, it suggests that both the federal government and the provinces should accept that international trade regulation, as a subject of national concern, is inseparable from the regulation of the internal economy, and as such should be considered as a question of mutual interest.